‘Megafire’—You May Not Like It, But You Cannot Avoid It - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2025)
Aim The term ‘megafire’ is increasingly used to describe large fires worldwide. We proposed a size‐based definition of megafire—fires exceeding 10,000 ha arising from single or multiple related ignition events. A recent perspective in Global Ecology and Biogeography argues against a size‐based definition of megafire and suggest that the term is too emotive for scientific use. We highlight that many scientific terms originate from common terms. These terms are often defined once they enter the scientific lexicon, enhancing both scientific understanding and public communication. We argue that standardised definitions facilitate better prediction, preparation, and management of fire events. Location Worldwide. Time Period 2022–2023. Methods We conducted an updated structured review of the term ‘megafire’ and its use and definition in the peer‐reviewed scientific literature, collating definitions and descriptions and identifying the criteria frequently invoked to define the term. Results We demonstrate an increase in the use of ‘megafire’ in the scientific literature since our original definition in 2022, with many studies adopting the > 10,000 ha size‐based criterion. Main Conclusions We contend that abandoning the term is neither practical, possible, nor beneficial. Instead, consistent usage underpinned by clear definitions is essential. Adopting a clear, size‐based definition of megafire strengthens clarity and comparability across research and management practices globally. Precision in terminology is crucial for advancing research, improving communication, and informing effective fire management and policy.

Did the terrestrial planets of the solar system form by pebble accretion? - A. Morbidelli; T. Kleine; F. Nimmo (Earth and Planetary Science Letters, 2025)

Functional Traits of the World's Late Quaternary Terrestrial Mammalian Predators - Eamonn I. F. Wooster; Erick J. Lundgren; Mairin Balisi; Rhys T. Lemoine; Christopher J. Sandom; Jens‐Christian Svenning; John Rowan; Chris J. Jolly; Grant D. Linley; Mitchell. A. Cowan; Nick Wright; Dylan Westaway; et al. (Global Ecology and Biogeography, 2024)
Motivation Terrestrial predators play key roles in cycling nutrients, as well as limiting prey populations, and shaping the behaviour of their prey. Prehistoric, historic and ongoing declines of the world's predators have reshaped terrestrial ecosystems and are a topic of conservation concern. However, the availability of ecologically relevant predator functional traits is limited, hampering efforts to understand macroecological changes in this ecologically important functional group. Here, we present CarniTraits , a comprehensive open‐access functional trait database of all late Quaternary (~130,000 ybp) terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Main Types of Variables Contained Mammalian terrestrial predator functional traits including body mass, diet, scavenging, locomotion, cooperative hunting, hunting habitat, hunting method, bone consumption, temporal activity patterns, brain mass and encephalisation quotient. Spatial Location and Grain Global. Time Period and Grain Late Quaternary (the last ~130,000 years). Major Taxa and Level of Measurement All late Quaternary terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Software Format csv.

Variations in lunar elastic thickness from admittance spectral analysis - R.E. Maxwell; F. Nimmo (Icarus, 2023)

Identifying historical and future global change drivers that place species recovery at risk - William L. Geary; Ayesha I. T. Tulloch; Euan G. Ritchie; Tim S. Doherty; Dale G. Nimmo; Marika A. Maxwell; Adrian F. Wayne (Global Change Biology, 2023)
Ecosystem management in the face of global change requires understanding how co‐occurring threats affect species and communities. Such an understanding allows for effective management strategies to be identified and implemented. An important component of this is differentiating between factors that are within (e.g. invasive predators) or outside (e.g. drought, large wildfires) of a local manager's control. In the global biodiversity hotspot of south‐western Australia, small‐ and medium‐sized mammal species are severely affected by anthropogenic threats and environmental disturbances, including invasive predators, fire, and declining rainfall. However, the relative importance of different drivers has not been quantified. We used data from a long‐term monitoring program to fit Bayesian state‐space models that estimated spatial and temporal changes in the relative abundance of four threatened mammal species: the woylie ( Bettongia penicillata ), chuditch ( Dasyurus geoffroii ), koomal ( Trichosurus vulpecula ) and quenda ( Isoodon fusciventor ). We then use Bayesian structural equation modelling to identify the direct and indirect drivers of population changes, and scenario analysis to forecast population responses to future environmental change. We found that habitat loss or conversion and reduced primary productivity (caused by rainfall declines) had greater effects on species' spatial and temporal population change than the range of fire and invasive predator (the red fox Vulpes vulpes ) management actions observed in the study area. Scenario analysis revealed that a greater extent of severe fire and further rainfall declines predicted under climate change, operating in concert are likely to further reduce the abundance of these species, but may be mitigated partially by invasive predator control. Considering both historical and future drivers of population change is necessary to identify the factors that risk species recovery. Given that both anthropogenic pressures and environmental disturbances can undermine conservation efforts, managers must consider how the relative benefit of conservation actions will be shaped by ongoing global change.

What do you mean, ‘megafire’? - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2022)
Background ‘Megafire’ is an emerging concept commonly used to describe fires that are extreme in terms of size, behaviour, and/or impacts, but the term’s meaning remains ambiguous. Approach We sought to resolve ambiguity surrounding the meaning of ‘megafire’ by conducting a structured review of the use and definition of the term in several languages in the peer‐reviewed scientific literature. We collated definitions and descriptions of megafire and identified criteria frequently invoked to define megafire. We recorded the size and location of megafires and mapped them to reveal global variation in the size of fires described as megafires. Results We identified 109 studies that define the term ‘megafire’ or identify a megafire, with the term first appearing in the peer‐reviewed literature in 2005. Seventy‐one (~65%) of these studies attempted to describe or define the term. There was considerable variability in the criteria used to define megafire, although definitions of megafire based on fire size were most common. Megafire size thresholds varied geographically from > 100–100,000 ha, with fires > 10,000 ha the most common size threshold (41%, 18/44 studies). Definitions of megafire were most common from studies led by authors from North America (52%, 37/71). We recorded 137 instances from 84 studies where fires were reported as megafires, the vast majority (94%, 129/137) of which exceed 10,000 ha in size. Megafires occurred in a range of biomes, but were most frequently described in forested biomes (112/137, 82%), and usually described single ignition fires (59% 81/137). Conclusion As Earth’s climate and ecosystems change, it is important that scientists can communicate trends in the occurrence of larger and more extreme fires with clarity. To overcome ambiguity, we suggest a definition of megafire as fires > 10,000 ha arising from single or multiple related ignition events. We introduce two additional terms – gigafire (> 100,000 ha) and terafire (> 1,000,000 ha) – for fires of an even larger scale than megafires.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Linear habitats in rural landscapes have complementary roles in bird conservation - Mark Hall; Dale Nimmo; Simon Watson; Andrew F. Bennett (Biodiversity and Conservation, 2018)

Landscape properties mediate the homogenization of bird assemblages during climatic extremes - Angie Haslem; Dale G. Nimmo; James Q. Radford; Andrew F. Bennett (Ecology, 2015)
Extreme weather events, such as drought, have marked impacts on biotic communities. In many regions, a predicted increase in occurrence of such events will be imposed on landscapes already heavily modified by human land use. There is an urgency, therefore, to understand the way in which the effects of such events may be exacerbated, or moderated, by different patterns of landscape change. We used empirical data on woodland‐dependent birds in southeast Australia, collected during and after a severe drought, to document temporal change in the composition of bird assemblages in 24 landscapes (each 100 km 2 ) representing a gradient in the cover of native wooded vegetation (from 60% to and that occurring in productive parts of the landscape, for maintaining bird communities whose composition is resistant to severe drought. While extreme climatic events cannot be prevented, their effects can be ameliorated by managing the pattern of native vegetation in anthropogenic landscapes, with associated benefits for maintaining ecological processes and human well‐being.

Continental‐Scale Governance and the Hastening of Loss of Australia's Biodiversity - Euan G. Ritchie; Corey J. A. Bradshaw; Chris R. Dickman; Richard Hobbs; Christopher N. Johnson; Emma L. Johnston; William F. Laurance; David Lindenmayer; Michael A. McCarthy; Dale G. Nimmo; Hugh H. Possingham; Robert L. Pressey; et al. (Conservation Biology, 2013)

Fire Mosaics and Reptile Conservation in a Fire‐Prone Region - D. G. NIMMO; L. T. KELLY; L. M. SPENCE‐BAILEY; S. J. WATSON; R. S. TAYLOR; M. F. CLARKE; A. F. BENNETT (Conservation Biology, 2013)
Fire influences the distribution of fauna in terrestrial biomes throughout the world. Use of fire to achieve a mosaic of vegetation in different stages of succession after burning (i.e., patch‐mosaic burning) is a dominant conservation practice in many regions. Despite this, knowledge of how the spatial attributes of vegetation mosaics created by fire affect fauna is extremely scarce, and it is unclear what kind of mosaic land managers should aim to achieve. We selected 28 landscapes (each 12.6 km 2 ) that varied in the spatial extent and diversity of vegetation succession after fire in a 104,000 km 2 area in the semiarid region of southeastern Australia. We surveyed for reptiles at 280 sites nested within the 28 landscapes. The landscape‐level occurrence of 9 of the 22 species modeled was associated with the spatial extent of vegetation age classes created by fire. Biogeographic context and the extent of a vegetation type influenced 7 and 4 species, respectively. No species were associated with the diversity of vegetation ages within a landscape. Negative relations between reptile occurrence and both extent of recently burned vegetation (≤10 years postfire, n = 6) and long unburned vegetation (>35 years postfire, n = 4) suggested that a coarse‐grained mosaic of areas (e.g. >1000 ha) of midsuccessional vegetation (11–35 years postfire) may support the fire‐sensitive reptile species we modeled. This age class coincides with a peak in spinifex cover, a keystone structure for reptiles in semiarid and arid Australia. Maintaining over the long term a coarse‐grained mosaic of large areas of midsuccessional vegetation in mallee ecosystems will need to be balanced against the short‐term negative effects of large fires on many reptile species and a documented preference by species from other taxonomic groups, particularly birds, for older vegetation. Mosaicos de Fuego y la Conservación de Reptiles en una Región Propensa al Fuego

Predicting the century‐long post‐fire responses of reptiles - Dale. G. Nimmo; Luke T. Kelly; Lisa M. Spence‐Bailey; Simon J. Watson; Angie Haslem; John G. White; Mike F. Clarke; Andrew F. Bennett (Global Ecology and Biogeography, 2012)
Aim We examined the century‐long post‐fire responses of reptiles to (1) determine the time‐scales over which fauna – fire relationships occur, (2) assess the capacity of a conceptual model to predict faunal response to fire, and (3) investigate the degree to which models of fauna – fire relationships can predict species occurrence and are transferable across space. Location A 104,000 km 2 area in the semi‐arid Murray Mallee region of south‐eastern Australia. Methods We surveyed reptiles at 280 sites across a century‐long post‐fire chronosequence. We developed generalized additive mixed models (GAMMs) of the relationship between time since fire and the occurrence of 17 species in two subregions, and compared modelled responses with predictions derived from the conceptual model. The predictive capacity of GAMMs was then assessed (1) within the subregion the model was developed and (2) when transferred into a novel subregion. Results Eleven species displayed a significant relationship with time‐since‐fire, with changes in species probability of occurrence continuing up to 100 years post‐fire. Predictions of the timing of species post‐fire peak in occurrence were accurate for 9 of 13 species models for which a significant fire response was detected, but little success was achieved in predicting the shape of a species' response. GAMMs predicted species occurrence more accurately when applied within the subregion in which they were developed than when transferred into a novel subregion, primarily due to some species responding to fire more strongly in one part of their geographic range. Main conclusions Fire influences the occurrence of reptiles in semi‐arid ecosystems over century‐long time frames. Habitat‐use conceptual models have value in predicting the peak occurrence of species following fire, particularly for species with distributions strongly shaped by fire. Species relationships with fire can differ across their geographic range, probably associated with variation in climatic influences on post‐fire succession and the consequent provision of habitat resources.

Epidemiology of non-multiresistant methicillin-resistant Staphylococcus aureus infection in Queensland, Australia: associations with indigenous populations and Panton–Valentine leukocidin - G. R. Nimmo; J. M. Schooneveldt; J. L. Sutherland; S. Power; D. Olesen; C. Selvey; F. Beard; M. Jones; D. L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

First outbreak of PVL-positive nonmultiresistant MRSA in a neonatal ICU in Australia: comparison of MALDI-TOF and SNP-plus-binary gene typing - S. Schlebusch; G. R. Price; S. Hinds; C. Nourse; J. M. Schooneveldt; M. H. Tilse; H. G. Liley; T. Wallis; F. Bowling; D. Venter; G. R. Nimmo (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Prevalence of Staphylococcus aureus strains in an Australian cohort, 1989–2003: evidence for the low prevalence of the toxic shock toxin and Panton–Valentine leukocidin genes - S. Schlebusch; J. M. Schooneveldt; F. Huygens; G. R. Nimmo (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Methicillin-susceptible, non-multiresistant methicillin-resistant and multiresistant methicillin-resistant Staphylococcus aureus infections: a clinical, epidemiological and microbiological comparative study - W. J. Munckhof; G. R. Nimmo; J. Carney; J. M. Schooneveldt; F. Huygens; J. Inman-Bamber; E. Tong; A. Morton; P. Giffard (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Effects of Metal Mining and Milling on Boundary Waters of Yellowstone National Park, USA - DELWAYNE R. NIMMO; MARY J. WILLOX; TOBEN D. LAFRANCOIS; PHILLIP L. CHAPMAN; STEPHEN F. BRINKMAN; JOSEPH C. GREENE (Environmental Management, 1998)